Learner-centred teaching and learning practices in geography teaching in Namibian secondary schools - Ockhuizen, John Abraham (University of the Free State, 2018)
After Namibia’s independence and with an educational reform where there was a shift from teacher-centred to learner-centred education by the Ministry of Basic Education and Culture in 1995, the purpose of the study was to establish whether, after more than twenty years of independence, the practices of learner-centred teaching and learning in Geography at senior secondary schools were practiced. There was a shift from teacher- to learner-centred education. Swartz and Avenstrup indicate that education in Namibia before Independence was highly content-orientated, and characterized by rote learning rather than inviting creativity and critical thinking. Swartz and van Graan further indicate that neither lecturers nor students applied the broad understanding of learner-centredness. The research questions addressed the following objectives: To determine the nature of learner-centred education in Namibian secondary schools; to determine the extent to which teachers applied learner-centredness in their teaching; to determine the extent to which learners interacted and communicated in a learner-centred approach; to determine the extent to which learning is taking place in a learner-centred approach; to determine the factors that did not contribute to the success of learner-centred teaching and learning in Namibian secondary schools; to determine whether classroom layout was conducive for learner-centred teaching. The population for the study comprised 560 secondary school learners from 17 secondary schools from nine educational regions in Namibia who were taking the subject Geography at either higher or ordinary level. The final sample which consisted of both males and females comprised 560 learners. There were 17 teacher consist of both male and female, teaching the subject Geography, on both higher and ordinary level. Seventeen school principals, both female and male, were included. The data were collected by making use of questionnaires for both Geography teachers and learners taking Geography as a school subject. Classroom observations were done at seventeen senior secondary schools in nine educational regions in Namibia. Interviews were held, involving both principals and teachers teaching Geography at the senior secondary level. To analyze the data, the SPSS program was used. Furthermore, frequencies and cross tabulation were also used to analyze the data. Cross tabulations were carried out for each of the sub-samples namely, gender, age and resources. The principle findings in the research are as follows: There is a great prevalence of teacher-centred teaching and learning. However, the teachers had a reasonably good understanding of learner-centred education, in contrast with that of the Geography senior secondary learners. The teachers dominated most of the instructional processes and practices. Even where teachers applied group activities or role play activities, there was no effective guidance or facilitation of the group activities. The learners merely reflected on the facts from the textbooks or teacher notes. Most of the time the teachers posed questions contrary to the learner-centred approach. The instruction of lessons was dictated by the subject curriculum and relevant subject materials, such as subject syllabuses, textbooks and teachers’ lesson notes on the chalk boards. There was effective communication between learners and teachers through the medium of English. Only in one school did learners address the teachers through their mother tongue. The Geography syllabus for Grades Eleven and Twelve was characterized by too many topics to be covered. The syllabus in itself was too much examination-driven. Preparation was at all times focused on what would be in the final examinations. Little time was allotted to knowledge construction and daily experiences. The main focus was on class tests, assignments or projects and external or final examinations. There were not many critical thinking exercises or problem-solving activities. In most cases homework was either examples of textbook activities or questions from previous examination papers. The researcher has made recommendations on in-service training regarding the implementation of LCE approaches: overcrowded classes; the lack of teaching resources; teachers’ use of integrated-formative evaluation and assessment approaches and, equally importantly, the need for further research around the influence of national examinations on effectively teaching in a learner-centred approach.

Na Namibië se onafhanklikheidswording en met die hervorming van opvoedkunde was daar ‘n verskuiwing vanaf onderwyser- na leerling-gesentreerdheid by die Ministerie van Basiese Onderwys en Kultuur in 1995. Die doel van hierdie studie was om te bepaal of daar, 20 jaar ná onafhanklikheid, werklik leerling-gesentreerde onderrig toegepas word in die onderrig van Aardrykskunde. Swartz en Avenstrup het aangedui dat onderwys vóór onafhanklikheid hoog inhouds-georiënteerd was en gekenmerk was deur roetine-leer eerder as dat kreatiwiteit en kritiese denke gebruik was. Swartz en van Graan het ook verder aangedui dat nóg dosente nóg studente die begrip leerling-gesentreerdheid in hulle onderrig toegepas het. Die navorsingsvrae sluit die volgende doelwitte in: Om die aard van leerling-gesentreerdheid in Namibiese sekondêre skole vas te stel; om die omvang van die toepassing van leerling-gesentreerdheid in die aanbieding van lesse vas te stel; om die omvang vas te stel van hoe ver leerlinge interaksie het en kommunikeer in ‘n leerling- gesentreerde klaskamer; om die omvang van die deelname aan ‘n leerling-gesentreerde benadering te bepaal; om die faktore te bepaal wat nie bydra tot die sukses van leerling-gesentreerde onderwys in Namibiese sekondêre skole nie; om vas te stel of die klaskamer uitleg in Namibiese skole geskik is vir leerling-gesentreerde onderwys. Die populasie vir die studie was saamgestel uit 560 sekondêre skool leerlinge wat Aardrykskunde doen as ‘n vak, hetsy op gewone of hoër vlak. Al die leerlinge kom uit die 17 sekondêre skole van die nege streke in Namibië. Die finale monster wat bestaan het uit manlike sowel as vroulike leerlinge was altesaam 560. Daar was ook 17 manlike en vroulike onderwysers wat Aardrykskunde as ‘n vak op beide hoër en gewone vlak aanbied. Die skoolhoofde wat deelgeneem het was saamgestel uit beide manlike sowel as vroulike persone, en was 17 in totaal. Die data was ingesamel deur gebruik te maak van vraelyste vir beide Aardrykskunde onderwysers en leerlinge. Klaskamer obserwasies was gedoen by 17 senior sekondêre skole dwarsoor die nege opvoedkunde streke in Namibië. Onderhoude was gevoer met skoolhoofde, sowel as onderwysers wat Aardrykskunde as ‘n vak op senior sekondêre vlak aanbied. Om die data te analiseer was die SPSS program gebruik. Frekwensies en kruis-tabulering was gebruik vir data analise. Kruis-tabulerings was gebruik vir elk van die sub-monsters, naamlik geslag, ouderdom en hulpbronne. Die hoof bevindinge in die navorsing is as volg: Daar is ‘n groot voorkoms van onderwyser-gesentreerde onderwys en leer. Die onderwysers het ‘n redelike goeie begrip van leerling-gesentreerde onderwys in teenstelling met dié van die senior sekondêre Aardrykskunde leerlinge. Die onderwysers domineer meestal die instruksies en lesaanbiedinge. Daar was geen riglyne of fasilitering gedurende groepsaktiwiteite of rolspel-aktiwiteite nie. Die leerlinge het weinig gereflekteer op die feite van die handboeke of onderwysers se notas. Die meeste van die tyd het die onderwysers vrae gevra ná die lesaanbieding wat in teenstelling was met ‘n leerling-gesentreerde benadering. Die instruksies van die lesse was gedikteer deur die vak-kurrikulum en relevante material soos vak-sillabusse, handboeke en die onderwysers se notas op die skryfbord. Daar was effektiewe kommunikasie tussen leerlinge en die onderwysers deur die medium van Engels. Daar was net een skool waar die leerlinge die onderwysers aangespreek het in hul moedertaal. Die Aardrykskunde sillabusse vir Graad 11 en 12 was gekenmerk deur te veel onderwerpe wat behandel word. Die sillabus self was te veel eksamen-gedrewe. Voorbereiding was te alle tye gefokus op moontlike vrae wat in die finale eksamen sou wees. Baie min tyd was gebruik om kennis en daaglikse ondervindings te genereer. Die hooffokus was op klastoetse, werkstukke en die eksterne of finale eksamens. Daar was nie baie oefening in kritiese denke of probleemoplossing nie. In die meeste gevalle was tuiswerk voorbeelde van óf handboek-aktiwiteite of vrae uit vorige vraestelle. Die navorser het aanbevelinge gemaak vir in-diensopleiding ten opsigte van die implementering van leerling-gesentreerde benaderings soos: oorvol klaskamers, ‘n tekort aan hulpbronne, onderwysers se gebruik van geintregeerde formatiewe evaluasie en assessering. Ewe belangrik ook is die behoefte vir verdere navorsing rondom die invloed van nasionale eksamens deur effektiewe, leerling-gesentreerde onderwys aan te bied.
Thesis (Ph.D. (Curriculum Studies))--University of the Free State, 2018
Keywords: Learner-centred; Teacher-centred; Classroom practice; Teacher training; Secondary schools; Critical thinking; Problem solving; Constructivism; Instructional resources; Teaching methods and techniques; Ministry of education